KAJIAN PENGEMBANGAN HOME INDUSTRI LANTING DI DESA KARANG BINANGUN KECAMATAN BELITANG MADANG RAYA KABUPATEN OKU TIMUR - Pudiyaka (Jurnal Bakti Agribisnis, 2016)
The purpose of this research is to: (1) To know the value added of lanting home industry in Karang Binangun Village Belitang District Madang Raya Regency OKU Timur, (2) To know the profit level of lanting home industry in Karang Binangun Village Belitang District Madang Raya OKU Regency East, (3) To know the amount of contribution given from home industry lanting to household income in Karang Binangun Village Belitang District Madang Raya Regency OKU East Regency OKU East. This research was conducted in Karang Binangun Village Belitang Madang Raya District, OKU Timur Regency. Determining the location intentionally (purposive sampling) with the consideration that in the Village Karang Binangun Belitang District Madang Raya OKU Timur Regency is one of the villages that seek home industry lanting. This research was conducted in July 2014. This research found that home industry lanting give added value for respondents in Karang Binangun Village Belitang Madang Raya District, OKU Timur Regency, that is Rp 5,777,92 / Kg. The average income from home industry lanting in Karang Binangun Village is Rp. 261,614.11 / production process, R / C ratio of 1.81, and B / C ratio is 0.81 and Contribution value of business making of lanting to family income is 66,98%.